Office space at Dearborn Chemical Company - Dearborn Chemical Company (1927)
General view of an office space at the Dearborn Chemical Company 35th Street laboratory facilities located in Chicago, Illinois. A partial view of one of the laboratory spaces is visible through the doorway. The employee seated at the desk is identified as E.P. Fager. The other two individuals visible in the photograph are unidentified. Founded in 1887, the Dearborn Chemical Company was a corporate ancestor of BetzDearborn, Incorporated best known for manufacturing water treatment chemicals for use in boilers, cooling towers, and steam locomotives.
Keywords: Employees; Chemical industry; Dearborn Chemical Company; Corporations; Women employees